Supply Chain Agility of E-Commerce Industry in Gaining Customer Trust - Atmaja, Diyaa Aaisyah Salmaa Putri; Nuryakin, Nuryakin; Pribadi, Firman (International Journal of Science, Technology & Management, 2022)
Supply chain agility is a supply chain capability derived from the intelligence, mindset, and integrative processes of all supply chain members to respond quickly to uncertainties and changes in the business environment in a reactive, proactive and predictive manner in meeting customer needs and demands. However, not all business people can perform system integration due to limited resources. In this case, the features presented by e-commerce can bridge business actors to achieve customer-centered supply chain agility competencies. This study aims to determine the effect of supply chain agility on the creation of customer trust which is supported by the use of e-tracing in the e-commerce industry. This approach uses multivariate analysis using SEM-PLS to determine the effect of each variable. Respondents were obtained by purposive random sampling technique and the survey was conducted online via Google Form aimed at the final 251 customers. The results show that supply chain agility has a positive and significant impact on customer trust. However, in this case, e-tracing has not been proven to strengthen or weaken the influence of supply chain agility on customer trust.